2017
DOI: 10.3892/etm.2017.5126
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‑related peptide has protective effect on brain injury induced by heat stroke in rats

Abstract: Heat stroke often leads to multiple organ dysfunction syndrome (MODS) with a neurological morbidity of 30%. Current studies suggested that pathophysiological responses to heat stroke may be due to a systemic inflammatory response syndrome and a series of peptidergic nerve reactions. The mechanisms underlying the high neurological morbidity in heat stroke have remained largely elusive. In recent years, calcitonin gene-related peptide (CGRP) has been considered to have a positive role in central nervous system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…For surviving patients, neurological sequelae are also an important factor in the quality of life. In our previous studies, we found that neuronal apoptosis is an important basis for brain injury in heat stroke ( 9 , 10 ). However, due to the particular intracranial structure and complex interactions between cells, the pathophysiological mechanism of brain injury in the HS is still unclear, which is a significant difficulty in treating heatstroke.…”
Section: Discussionmentioning
confidence: 97%
“…For surviving patients, neurological sequelae are also an important factor in the quality of life. In our previous studies, we found that neuronal apoptosis is an important basis for brain injury in heat stroke ( 9 , 10 ). However, due to the particular intracranial structure and complex interactions between cells, the pathophysiological mechanism of brain injury in the HS is still unclear, which is a significant difficulty in treating heatstroke.…”
Section: Discussionmentioning
confidence: 97%
“…CGRP expression is high in the CNS suggesting neurotransmitter activity. CGRP was shown to provide significant protective properties in different experimental systems, including heat injury and ischemia/reperfusion in rats and overexpression in Schwann cells subject to oxidative stress (Russell et al, 2014; Wu et al, 2015; Yang et al, 2016; Lu et al, 2017). Secretogranin II (SCG2)(Chromagranin C) is also a neuroendrocrine secretory protein that is cleaved to form the peptide secretoneurin.…”
Section: Discussionmentioning
confidence: 99%
“…However, intramyocardial injection of adenovirus encoding the CGRP gene reduced myocardial infarct size and plasma LDH level in both non-diabetic and diabetic mice (Zheng et al, 2012). α-CGRP has been shown to prevent I/R damage in other tissues such as the intestines, kidneys, and brain (Song et al, 2009;Liu et al, 2011;Lu et al, 2017). When central organs, like the heart and liver, are exposed to ischemia, α-CGRP release may serve to both prevent damage to these organs and protect other organ systems, such as the intestines, from subsequent injury via reflexive neuronal release.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%